2023
DOI: 10.3390/pharmaceutics15010292
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Iron Oxide Nanoparticles Loaded with Doxorubicin for Combined Chemo-Photothermal Cancer Therapy

Abstract: Iron oxide nanoparticle (IONP) possesses unique advantages over other nanoparticles in the use of cancer imaging and therapy. Specifically, it has drawn great attention in the emerging research field of photothermal cancer therapy. Herein, we developed doxorubicin (DOX)-loaded liposomal IONP (Lipo-IONP/DOX) and evaluated in vitro and in vivo their applicability for combined chemo-photothermal cancer therapy. The Lipo-IONP was synthesized by the thin-film evaporation method. The prepared Lipo-IONP was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Park et al developed doxorubicin-loaded liposomal iron oxide nanoparticles and evaluated their application in vitro and in vivo for combined chemo-photothermal cancer therapy. Finally, after studying the initial efficacy, utility, and safety of their nanosystem, they reported that it may serve as an effective and safe agent for combination cancer therapy [ 30 ]. Electron microscopy images showed a proper morphology of the spherical and smooth liposomes ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…Park et al developed doxorubicin-loaded liposomal iron oxide nanoparticles and evaluated their application in vitro and in vivo for combined chemo-photothermal cancer therapy. Finally, after studying the initial efficacy, utility, and safety of their nanosystem, they reported that it may serve as an effective and safe agent for combination cancer therapy [ 30 ]. Electron microscopy images showed a proper morphology of the spherical and smooth liposomes ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…Tian等 [123] . (d) Lipo-IONP/DOX在磁引导和光触 发下进行光热和化学联合治疗癌症 [124] (网络版彩图) 纳米颗粒团聚体Lipo-IONP. 该脂质体既可负载亲水性 药物, 又可负载疏水性药物, 已作为临床递送化疗药物 的载体 [125] .…”
Section: 与其他金属基纳米粒子相比 氧化铁纳米粒子unclassified
“…Although the FDA has approved several ION formulations, specific unwanted toxicity issues reported in many studies that could be overcome by functionalization and surface modification with various coverage and ligands would be helpful to improve their circulation time, clearance, and evasion by reticuloendothelial system, as well as improving tissue targeting, biocompatibility, and stability [74][75][76][77][78]. It has now been demonstrated that [79] the doxorubicin (DOX)-loaded liposomal iron oxide NPs (IONP) (Lipo-IONP/DOX) might serve as a safe and effective agent for combined chemo/photothermal cancer therapy. Currently, iron oxide NPs are the ideal agents for cancer theranostics.…”
Section: Iron-based Nanoparticlesmentioning
confidence: 99%